2007
DOI: 10.1017/s147106840700316x
|View full text |Cite
|
Sign up to set email alerts
|

Linear tabling strategies and optimizations

Abstract: Recently there has been a growing interest of research in tabling in the logic programming community because of its usefulness in a variety of application domains including program analysis, parsing, deductive databases, theorem proving, model checking, and logic-based probabilistic learning. The main idea of tabling is to memorize the answers to some subgoals and use the answers to resolve subsequent variant subgoals. Early resolution mechanisms proposed for tabling such as OLDT and SLG rely on suspension and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…In fact, there exist a library for graph algorithms also in SICStus, while in B-Prolog the table mode (Warren 1992;Zhou et al 2008) lets one easily implement efficient graph predicates. Unluckily, the syntax of ECL i PS e and SICStus/B-Prolog is different, although similar; for example, although both ECL i PS e (Schimpf 2002) and B-Prolog (Zhou 2011) support logical loops, they adopt a different syntax.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there exist a library for graph algorithms also in SICStus, while in B-Prolog the table mode (Warren 1992;Zhou et al 2008) lets one easily implement efficient graph predicates. Unluckily, the syntax of ECL i PS e and SICStus/B-Prolog is different, although similar; for example, although both ECL i PS e (Schimpf 2002) and B-Prolog (Zhou 2011) support logical loops, they adopt a different syntax.…”
Section: Discussionmentioning
confidence: 99%
“…B-Prolog is a tabled Prolog system that is based on linear tabling [19], allows variant subgoals to share answers, and uses the local strategy [9] (also called lazy strategy [19]) to return answers. In B-Prolog, tabled predicates are declared explicitly by declarations in the following form:…”
Section: Tabling In B-prologmentioning
confidence: 99%
“…Tabling, as provided in logic programming systems such as B-Prolog (Zhou et al 2008), XSB (Swift and Warren 2012), YAP (Santos Costa et al 2012), and Mercury (Somogyi and Sagonas 2006), has been shown to be a viable declarative language construct for describing dynamic programming solutions for various kinds of realworld applications, ranging from program analysis, parsing, deductive databases, theorem proving, model checking, to logic-based probabilistic learning. The main idea of tabling is to memorize the answers to subgoals in a table area and use the answers to resolve their variant or subsumed descendants.…”
Section: Introductionmentioning
confidence: 99%